Heat seal paper

The heat seal paper, featuring a PHBH heat seal layer anchored by an ethylene-vinyl acetate copolymer resin coating layer, addresses the issues of weak adhesion and peeling in biodegradable plastics, achieving excellent interlayer adhesion and reliable heat sealing.

JP2025059333AActive Publication Date: 2025-04-10NIPPON PAPER IND CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023169372
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10
Estimated Expiration
2043-09-29

AI Technical Summary

Technical Problem

Existing biodegradable plastics, such as aliphatic polyesters, have slow biodegradation rates at low temperatures, while poly(3-hydroxybutyrate) resins suffer from weak adhesion when laminated directly on paper, leading to peeling issues.

Method used

A heat seal paper is developed with a laminated heat seal layer made of PHBH film, anchored by an ethylene-vinyl acetate copolymer resin coating layer, which enhances interlayer adhesion and prevents peeling.

Benefits of technology

The heat seal paper achieves excellent interlayer adhesion, reducing peeling between layers and allowing for reliable heat sealing, making it suitable for various packaging forms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059333000001
    Figure 2025059333000001
Patent Text Reader

Abstract

To provide heat seal paper having a film which is excellent in adhesion of a laminate layer and contains PHBH as a main component.SOLUTION: There is provided heat seal paper in which a heat seal layer composed of a film containing PHBH (poly(3-hydroxybutylate-co-3-hydroxyhexanoate)) as a main component is bonded to at least one surface of a paper base material through an anchor layer, wherein the anchor layer is a coating layer containing an ethylene-vinyl acetate copolymer resin.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat seal paper. [Background technology]

[0002] In recent years, efforts have begun to prevent environmental destruction caused by plastic waste, and there is a demand to replace disposable plastic products with materials that have a smaller impact on the environment. Alternative materials to plastic include biodegradable plastics, wood, paper, etc. Aliphatic polyesters such as polylactic acid and polycaprolactone are known as biodegradable plastics. However, aliphatic polyesters have the problem that they take a long time to biodegrade at low temperatures and decompose slowly in natural environments such as the ocean. On the other hand, poly(3-hydroxybutyrate)-based resins are microbially produced thermoplastics that are highly degradable under aerobic and anaerobic conditions, and have the remarkable ability of being degraded by microorganisms in a short period of time even in water such as the ocean. Patent Document 1 describes that a biodegradable polyester aqueous dispersion containing poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (hereinafter also referred to as PHBH), which is a copolymer of 3-hydroxybutyrate and 3-hydroxyhexanoate, has excellent film-forming properties and gives a resin coating film that is flexible, stretchable, and resistant to bending when applied to paints, adhesives, fiber processing, sheet / film processing, paper processing, etc.

[0003] Patent Document 2 proposes an invention of a laminate in which this PHBH is laminated on at least one side of a lamination substrate such as paper, and describes in the examples that a laminate is obtained by melt extrusion laminating PHBH. However, when PHBH is directly laminated onto paper, there is a problem that the adhesive strength between the paper and the PHBH layer is weak, and when PHBH layers are laminated together for use as a packaging material, etc., peeling is likely to occur at the interface between the paper and the PHBH layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2004 / 041936 [Patent Document 2] Japanese Patent Application Publication No. 10-128920 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a heat seal paper having a film mainly composed of PHBH, which has excellent adhesion to a laminate layer. [Means for solving the problem]

[0006] The means for solving the problems of the present invention are as follows. 1. A heat seal layer made of a film mainly composed of PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)) is attached to at least one surface of a paper substrate via an anchor layer; 13. A heat sealable paper, wherein the anchor layer is a coating layer containing an ethylene-vinyl acetate copolymer resin. 2. The heat sealable paper according to 1, wherein the molar ratio of ethylene to vinyl acetate in the ethylene-vinyl acetate copolymer resin is 50:50 to 6:94. 3. The heat sealable paper according to 1 or 2, wherein the ethylene-vinyl acetate copolymer resin has a glass transition temperature of -50 to 30°C. Effect of the Invention

[0007] The heat seal paper of the present invention has excellent interlayer adhesion and is less susceptible to peeling between the paper base material and the anchor layer, and between the anchor layer and the heat seal layer. The heat seal paper of the present invention can be made into various types of packaging materials by heat sealing processing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The heat seal paper of the present invention has a heat seal layer made of a film mainly composed of PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)) bonded to at least one surface of a paper substrate via an anchor layer; The anchor layer is characterized in that it is a coating layer containing an ethylene-vinyl acetate copolymer resin. In this specification, the expression "A to B" (A and B are numerical values) means a numerical range including A and B, that is, "A or more and B or less."

[0009] (Paper base material) The paper base material is a sheet (hereinafter also referred to as "base paper") mainly made of pulp, and is obtained by making paper from a stock that further contains fillers, various auxiliaries, and the like. Pulp may be selected from chemical pulps such as bleached hardwood kraft pulp (LBKP), bleached softwood kraft pulp (NBKP), unbleached hardwood kraft pulp (LUKP), unbleached softwood pulp (NUKP), sulfite pulp, and other mechanical pulps, wood fibers such as deinked pulp and waste paper pulp, and non-wood fibers obtained from kenaf, bamboo, hemp, and the like, which may be used in appropriate combinations. Among these, it is preferable to use chemical pulp of wood fiber or mechanical pulp of wood fiber, and it is more preferable to use chemical pulp of wood fiber, for reasons such as the fact that foreign matter is unlikely to be mixed into the paper base material, that discoloration is unlikely to occur over time when recycled as waste paper raw material, that the surface texture is good when printed due to high whiteness, and that the value of use is particularly high when used as a packaging material. Specifically, the amount of chemical pulp such as LBKP or NBKP relative to the total pulp is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 100% by mass.

[0010] Examples of fillers that can be used include inorganic fillers such as talc, kaolin, calcined kaolin, clay, heavy calcium carbonate, light calcium carbonate, white carbon, zeolite, magnesium carbonate, barium carbonate, titanium dioxide, zinc oxide, silicon oxide, amorphous silica, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, barium sulfate, and calcium sulfate, and organic fillers such as urea-formalin resin, polystyrene resin, phenolic resin, and hollow microparticles. Note that fillers are not essential materials and may not be used.

[0011] Examples of various auxiliary agents include sizing agents such as rosin, alkyl ketene dimer (AKD), alkenyl succinic anhydride (ASA), polyacrylamide polymers, polyvinyl alcohol polymers, cationic starch, various modified starches, urea-formaldehyde resin, melamine-formaldehyde resin, and other dry strength agents, wet strength agents, retention agents, drainage improvers, coagulants, aluminum sulfate, bulking agents, dyes, fluorescent brighteners, pH adjusters, defoamers, UV inhibitors, anti-fading agents, pitch control agents, slime control agents, and the like, and can be selected and used as appropriate as needed.

[0012] The surface of the paper substrate may be treated with various chemicals. Examples of chemicals include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agents, water-resistant agents, water retention agents, thickeners, and lubricants, and these may be used alone or in combination of two or more. Furthermore, these various chemicals may be used in combination with pigments. Examples of pigments include inorganic pigments such as kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, and satin white, and organic pigments such as solid, hollow, and core-shell types may be used alone or in combination of two or more.

[0013] The basis weight of the paper base material can be selected appropriately depending on the desired quality and its application, but is usually 20 g / m 2 More than 600g / m 2 Less than 25 g / m is preferred. 2 More than 600g / m 2 The following is more preferred: For example, when used for packaging materials such as wrapping paper, paper bags, lids, and lining paper, and for posters to be used outdoors, the basis weight of the paper base material is 30 g / m 2 More than 150g / m 2 When used as a flexible packaging material, the paper base material preferably has a basis weight of 20 g / m 2 More than 100g / m 2 Less than 35 g / m is preferred. 2 More than 80g / m 2 The following is more preferable. The soft packaging material is, among the packaging materials, particularly, a material having a density of 20 g / m 2 From 100g / m 2 It is a flexible packaging material made of thin paper of about 150 g / m2. When used for paper cups, paper containers, paper boxes, paper plates, paper trays, etc., the basis weight of the paper base material is 150 g / m2. 2 More than 300g / m 2 The following is preferred: The density of the paper base material can be appropriately selected depending on the desired qualities and ease of handling, but is usually 0.5 g / cm 3 More than 1.0g / cm 3 The following are preferred:

[0014] The method of manufacturing (papermaking) the paper base material is not particularly limited, and known manufacturing (papermaking) methods and papermaking machines can be selected, such as a Fourdrinier papermaking machine, a cylinder papermaking machine, a short wire papermaking machine, a twin-wire papermaking machine such as a gap former type or a hybrid former type (on-top former type). The pH during papermaking may be in the acidic range (acidic papermaking), pseudo-neutral range (pseudo-neutral papermaking), neutral range (neutral papermaking), or alkaline range (alkaline papermaking), and after papermaking in the acidic range, an alkaline agent may be applied to the surface of the paper layer. The paper base material may be one layer, or may be composed of two or more layers. Furthermore, when treating the surface of a paper substrate with a chemical, the method of surface treatment is not particularly limited, and known coating devices such as a rod metering size press, a pond type size press, a gate roll coater, a spray coater, a blade coater, or a curtain coater can be used.

[0015] (Heat seal layer) The heat seal layer is made of a film containing PHBH as a main component. In the present invention, "containing PHBH as a main component" means that it contains 50% by mass or more. <phbh> PHBH is a copolymer of 3-hydroxybutyrate (hereinafter also referred to as 3HB) and 3-hydroxyhexanoate (hereinafter also referred to as 3HH), and is a biodegradable resin known to be produced by microorganisms. In the present invention, the PHBH used may be derived from microorganisms or petroleum resources, but it is preferable to use the PHBH derived from microorganisms in terms of reducing the environmental load.

[0016] Microorganisms that produce PHBH are not particularly limited as long as they accumulate PHBH intracellularly, but examples include bacteria of the genus Alcaligenes, such as A. lipolytica, A. eutrophus, and A. latus, as well as bacteria of the genus Pseudomonas, Bacillus, Azotobacter, Nocardia, and Aeromonas. Among them, in terms of productivity of PHBH, strains such as Aeromonas caviae, and Alcaligenes eutrophus AC32 (accession number FERM BP-6038, date of deposit on August 7, 1997, National Institute of Advanced Industrial Science and Technology, Patent Biological Deposit Center, address: Central 6, 1-1-1 Higashi, Tsukuba-shi, Ibaraki-ken, Japan) (J. Bacteriol., 179, pp. 4821-4830 (1997)) into which genes of PHA synthase group have been introduced are particularly preferred. A method for obtaining PHBH from Aeromonas caviae, a microorganism of the Aeromonas genus, is disclosed, for example, in Japanese Patent Publication No. 05-093049. These microorganisms are used by culturing them under appropriate conditions to accumulate PHBH in the cells. The carbon source and culture conditions used in the culture can be obtained according to the methods described in JP-A-05-093049, JP-A-2001-340078, etc., but are not limited thereto.

[0017] The composition ratio (mol%) of PHBH is preferably 3HB:3HH=97:3 to 75:25, more preferably 95:5 to 78:12, and even more preferably 93:7 to 80:20. If the composition of 3HH is less than 3 mol%, the properties of PHBH become similar to those of 3HB homopolymer, resulting in loss of flexibility and an excessively high film-forming processing temperature, which is undesirable. If the composition of 3HH exceeds 25 mol%, the crystallization rate becomes too slow to be suitable for film-forming processing, and the degree of crystallization decreases, making the resin flexible and tending to decrease the flexural modulus. The composition ratio of PHBH can be measured by a known method, for example, NMR analysis. Microbial PHBH is a random copolymer. To adjust the molar ratio of the copolymer, there are several methods, such as selecting the bacterial cells, selecting the carbon source as the raw material, blending with PHBH of different molar ratios, and blending with 3HB homopolymer.

[0018] In one embodiment of the present invention, the mass average molecular weight of PHBH is preferably 50,000 to 700,000, more preferably 100,000 to 600,000, and even more preferably 200,000 to 400,000. When the mass average molecular weight of PHBH is within the above range, a film with excellent mechanical properties can be obtained. The mass average molecular weight of PHBH can be determined as a molecular weight converted into polystyrene by gel permeation chromatography (GPC, such as "Shodex GPC-101" manufactured by Showa Denko K.K.) using polystyrene gel (such as "Shodex K-804" manufactured by Showa Denko K.K.) in a column and chloroform as a mobile phase. As a measurement sample, a powder obtained by centrifuging an aqueous dispersion containing PHBH and then drying it is used. In the present invention, two or more types of PHBH having different composition ratios, mass average molecular weights, etc. may be mixed and used.

[0019] In addition to PHBH, the heat seal layer may contain other thermoplastic resins, lubricants, inorganic fillers, plasticizers, antiblocking agents, odor absorbers, fragrances, antioxidants, antioxidants, weather resistance improvers, ultraviolet absorbers, crystal nucleating agents, release agents, water repellents, antibacterial agents, sliding improvers, colorants such as pigments and dyes, etc. However, the heat seal layer is mainly composed of PHBH, and the ratio of PHBH to the entire heat seal layer is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.

[0020] The other thermoplastic resin is not particularly limited as long as it is compatible with PHBH, but is preferably a biodegradable resin, and examples thereof include aliphatic polyester-based resins such as polycaprolactone, polybutylene succinate adipate, polybutylene succinate, and polylactic acid, and aliphatic aromatic polyester-based resins such as polybutylene adipate terephthalate and polybutylene azelate terephthalate.

[0021] As the lubricant, known lubricants can be used, and examples thereof include aliphatic amide compounds such as saturated or unsaturated fatty acid amides such as lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, oleic acid amide, and erucic acid amide, alkylene fatty acid amides such as methylene bisstearic acid amide and methylene bisstearic acid amide, and pentaerythritol. The amount of the lubricant to be added is preferably 0.1 to 2 parts by mass, and more preferably 0.2 to 1 part by mass, based on 100 parts by mass of PHBH.

[0022] Examples of inorganic fillers include those having an average particle size of 0.5 μm or more, such as talc, calcium carbonate, mica, silica, clay, kaolin, titanium oxide, alumina, and zeolite. The amount of the inorganic filler to be added is preferably 0.5 to 5 parts by mass, and more preferably 1 to 3 parts by mass, based on 100 parts by mass of PHBH.

[0023] (Anchor layer) The anchor layer is a coating layer containing an ethylene-vinyl acetate copolymer resin. It is preferable that the anchor layer is a coating layer of a water-dispersed paint from the viewpoint of reducing the burden on the environment during production. Whether or not the anchor layer is a coating layer can be determined by observing the cross section with an electron microscope or the like.

[0024] Ethylene-vinyl acetate copolymer resin Ethylene-vinyl acetate copolymer resin (hereinafter also referred to as EVA) is a copolymer having ethylene and vinyl acetate as monomers, and may further have other monomers as monomers. When EVA has other monomers as monomers, the content of structural units derived from other monomers in the whole EVA is preferably 30% by mass or less. This content is not particularly limited as long as it does not impair the effects of the present invention, and can be, for example, 20% by mass or less, 10% by mass or less, 5% by mass or less, 3% by mass or less, 1% by mass or less, etc.

[0025] The molar ratio of ethylene to vinyl acetate in the EVA (structural units derived from ethylene:structural units derived from vinyl acetate, also expressed as ethylene:vinyl acetate, the total being 100) is preferably 50:50 to 6:94 from the viewpoint of interlayer adhesion, more preferably 45:55 to 7:93, further preferably 40:60 to 8:92.

[0026] From the viewpoint of interlayer adhesion, the glass transition temperature of EVA is preferably −50 to 30° C. This glass transition temperature is more preferably −40 to 20° C., and further preferably −30 to 15° C. In this specification, the glass transition temperature is the midpoint glass transition temperature measured in accordance with JIS K 7121-1987.

[0027] The anchor layer may contain, in addition to EVA, other water-soluble resins and water-dispersible resins, and may further contain, as necessary, various auxiliaries that are blended into coating solutions in the papermaking field, such as dispersants, viscosity improvers, water retention agents, defoamers, water resistance agents, pH adjusters, cationic resins, anionic resins, UV absorbers, metal salts, lubricants, coloring dyes, pigments, etc. However, the anchor layer is preferably composed mainly of ethylene-vinyl acetate copolymer resin, and the proportion of the ethylene-vinyl acetate copolymer resin to the entire anchor layer (solid content) is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more.

[0028] <Method of manufacturing heat seal paper> The heat seal paper of the present invention can be produced by laminating a film containing PHBH as a heat seal layer to a paper substrate via an anchor layer. The heat seal layer can be provided on only one side or both sides of the paper substrate.

[0029] The coating method of the anchor layer is not particularly limited, and coating can be performed using a known coating device and coating system. For example, the coating device can be a blade coater, a bar coater, an air knife coater, a curtain coater, a spray coater, a roll coater, a reverse roll coater, a size press coater, a gate roll coater, etc., and the viscosity, solid content concentration, etc. of the coating liquid for the anchor layer can be appropriately adjusted depending on the coating device, coating system, etc. used. The coating amount (dry mass) of the anchor layer is not particularly limited as long as it can exhibit its performance. For example, it is 0.1 g / m per side. 2 More than 10.0g / m 2 The following is the result.

[0030] The film containing PHBH as a main component can be laminated onto the anchor layer by melt extrusion lamination. The thickness of the heat seal layer is not particularly limited, but is preferably, for example, 5 μm or more and 300 μm or less. If the thickness of the heat seal layer is less than 5 μm, the heat sealability may not be fully exhibited. If the thickness of the heat seal layer exceeds 300 μm, the heat seal layer becomes too rigid, which may reduce the processability as a heat seal paper and increase the cost. The thickness of the heat seal layer is preferably 10 μm or more, more preferably 20 μm or more, and preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 60 μm or less.

[0031] The heat seal paper of the present invention is easy to mold, maintain its shape, and ensure airtightness, and can therefore be suitably used for paper bags, paper containers, paper boxes, paper cups, (soft) packaging materials, lid materials, and the like. The heat seal paper of the present invention, in which the heat seal layer is also a water resistant layer, can be suitably used as wrapping paper, paper bags, paper containers, paper boxes, paper cups, (soft) packaging materials, paper plates, paper trays, posters for outdoor use, etc. The heat seal paper of the present invention, in which the heat seal layer is also an oil-resistant layer, can be suitably used as (soft) packaging materials or wrapping paper for foods that contain a lot of oil, such as hamburgers, hot dogs, French fries, fried chicken, potato chips, etc., as lining paper for fried foods such as tempura, paper plates, paper trays, paper cups, etc. EXAMPLES

[0032] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, parts and % are by mass, respectively, unless otherwise specified.

[0033] Paper base material: basis weight 220g / m 2 Cup base paper (product name: CUP-HD, manufactured by Nippon Paper Industries Co., Ltd.) Polyester resin: Z221, manufactured by GOO Chemical Industry Co., Ltd., Tg: 47℃ EVA1: Sumika Chemtex Co., Ltd., Sumika Flex S-201HQ, Tg-20℃, ethylene:vinyl acetate=30:70 EVA2: Sumika Chemtex Co., Ltd., Sumika Flex S-408HQE, Tg-30℃, ethylene:vinyl acetate=40:60 EVA3: Sumika Chemtex Co., Ltd., Sumika Flex S-410HQ, Tg-18℃, ethylene:vinyl acetate=30:70 EVA4: Sumika Chemtex Co., Ltd., Sumika Flex S-401HQ, Tg-18°C, ethylene:vinyl acetate=30:70 EVA5: Sumika Chemtex Co., Ltd., Sumika Flex S-400HQ, Tg 0°C, ethylene:vinyl acetate = 20:80 EVA6: Sumika Chemtex Co., Ltd., Sumika Flex S-355HQ, Tg 10°C, ethylene:vinyl acetate = 10:90 PHBH: Kaneka Corporation, mass average molecular weight 600,000

[0034] An aqueous dispersion of polyester resin or ethylene-vinyl acetate copolymer resin with a concentration of 23% by mass was applied to one surface of the paper substrate by the bar blade method, and dried at 105°C for 1 minute to form an anchor layer. On this anchor layer, PHBH having a mass average molecular weight of 600,000 was laminated by melt extrusion to a thickness of 30 μm to obtain a heat seal paper.

[0035] (Evaluation method) The heat seal paper thus obtained was subjected to the following evaluations, and the results are shown in Table 1. ·Laminate layer adhesion Two square test pieces with sides of 40 mm were cut out from the obtained heat seal paper, and the heat seal layers were brought into contact with each other and pressed at a pressure of 130°C and 1.5 kgf / cm. 2 The heat seal was performed with pressure applied for 3.0 seconds. A cutter blade was used to make a slit 2 mm deep in the heat seal layer, and the heat seal layer was manually peeled off from the slit. The force felt when peeling and the condition after peeling were visually observed and evaluated according to the following criteria. [Evaluation Criteria] 5: Material failure occurs (paper substrate is destroyed). 4: Partial material failure occurs (paper base material is destroyed). 3: There is a strong sense of resistance, but no breakage of the material occurs. 2: There is some resistance, but it can be peeled off easily. 1: It can be peeled off very easily without any resistance.

[0036] [Table 1]

[0037] The laminated papers obtained in the examples had excellent laminate layer adhesion. In particular, Examples 3-1, 3-2, 4-1, 4-2, 5-1, 5-2, 6-1, and 6-2 had excellent laminate layer adhesion and broke. The mechanism by which the heat seal paper obtained in the examples of the present invention has excellent laminate layer adhesion is unclear, but it is thought that the copolymerization ratio of ethylene and vinyl acetate, which are monomers that make up EVA, or the proportion of carbonyl groups and vinyl groups in a certain molecular weight of EVA, or the glass transition temperature of EVA may have an effect. In addition, when EVA is used as the anchor layer, the coating weight of the anchor layer is 1.0 to 1.6 g / m 2 In this case, the glass transition temperature is in the range of -18°C to 10°C, and the coating weight of the anchor layer is 2.7 to 3.6 g / m 2 When the concentration of EVA was increased to 10°C, the laminate layer adhesion rating of "5" was obtained in the glass transition temperature range of -30°C to 10°C. Since EVA has excellent laminate layer adhesion over a wide range of glass transition temperatures, it allows for a high degree of freedom in the selection of EVA when designing a formulation. Furthermore, EVA is also superior in that it can achieve high laminate layer adhesion with a smaller coating weight than the polyester disclosed as an anchor agent in Patent No. 7285387.< / phbh>

Claims

1. A heat seal layer made of a film mainly composed of PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)) is attached to at least one surface of the paper substrate via an anchor layer; The heat seal paper is characterized in that the anchor layer is a coating layer containing an ethylene-vinyl acetate copolymer resin.

2. 2. The heat seal paper according to claim 1, wherein the molar ratio of ethylene to vinyl acetate in the ethylene-vinyl acetate copolymer resin is from 50:50 to 6:

94.

3. 3. The heat seal paper according to claim 1, wherein the ethylene-vinyl acetate copolymer resin has a glass transition temperature of -50 to 30°C.

Citation Information

Patent Citations

  • Biodegradable heat insulating container

    JP2018162075A

  • Cellophane laminate

    JP2024039713A

  • heat seal paper

    JP7285387B1

  • Laminate and use thereof

    WO2021100733A1

  • Material for paper containers for liquid, paper container for liquid, paper container for liquid for aseptic filling, and method for producing recycled pulp

    WO2021182183A1